Edukasi Pijat Common Cold untuk Meningkatkan Pengetahuan Siswa Jurusan Layanan Kesehatan dan Caregiver di SMK Darussalam Bergas - Ida Sofiyanti; Luvi Dian Afriyani; Heni Setyowati (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2026)
Common cold is one of the upper respiratory tract disorders that frequently occurs in children and adolescents. The management of common cold can be carried out pharmacologically and non-pharmacologically, one of which is through common cold massage therapy. Based on the situational analysis conducted at SMK Darussalam Bergas, it was found that most students of the Health Services and Caregiver Department had limited understanding regarding the benefits and techniques of common cold massage as a complementary therapy to help relieve cough and cold symptoms. Therefore, the community service team from the Midwifery Study Program of Universitas Ngudi Waluyo conducted a community service activity in the form of education and training on common cold massage on December 16, 2025. The methods included situational analysis, health education using PowerPoint (PPT) media, massage demonstrations using x-banners and dolls, and direct practice by participants. Evaluation was conducted through pretests and posttests using questionnaires consisting of 10 questions related to common cold and common cold massage. The evaluation results showed an increase in the average participants’ knowledge score from 58.9% in the pretest to 95.8% in the posttest after the education and common cold massage practice sessions. Participants also demonstrated high enthusiasm throughout the activity. This program is expected to improve the competence of Health Services and Caregiver students in providing simple complementary therapy for common cold cases.   ABSTRAK Common cold merupakan salah satu gangguan saluran pernapasan atas yang sering terjadi pada anak dan remaja. Penatalaksanaan common cold dapat dilakukan secara farmakologis maupun nonfarmakologis, salah satunya melalui terapi pijat common cold. Berdasarkan hasil analisis situasi di SMK Darussalam Bergas, ditemukan bahwa sebagian besar siswa jurusan Layanan Kesehatan dan Caregiver belum memahami manfaat dan teknik pijat common cold sebagai terapi komplementer untuk membantu mengurangi keluhan batuk pilek. Oleh karena itu, tim pengabdian dari Program Studi Kebidanan Universitas Ngudi Waluyo melaksanakan kegiatan pengabdian kepada masyarakat berupa edukasi dan pelatihan pijat common cold pada tanggal 16 Desember 2025. Metode kegiatan meliputi analisis situasi, penyuluhan menggunakan media PowerPoint (PPT), demonstrasi pijat menggunakan x-banner dan boneka, serta praktik langsung oleh peserta. Evaluasi dilakukan melalui pretest dan posttest menggunakan kuesioner berisi 10 pertanyaan terkait common cold dan pijat common cold. Hasil evaluasi menunjukkan peningkatan rerata pengetahuan peserta dari 58,9% pada pretest menjadi 95,8% pada posttest setelah diberikan edukasi dan praktik pijat common cold. Peserta juga menunjukkan antusiasme tinggi selama kegiatan berlangsung. Program ini diharapkan dapat meningkatkan kompetensi siswa Layanan Kesehatan dan Caregiver dalam memberikan terapi komplementer sederhana pada kasus common cold.